Emerging contrast agents for multispectral optoacoustic imaging and their biomedical applications - Wu, Yinglong (2022)
Optoacoustic imaging is a hybrid biomedical imaging modality which collects ultrasound waves generated via photoexciting contrast agents in tissues and produces images of high resolution and penetration depth. As a functional optoacoustic imaging technique, multispectral optoacoustic imaging, which can discriminate optoacoustic signals from different contrast agents by illuminating samples with multi-wavelength lasers and then processing the collected data with specific algorithms, assists in the identification of a specific contrast agent in target tissues and enables simultaneous molecular and physiological imaging. Moreover, multispectral optoacoustic imaging can also generate threedimensional images for biological tissues/samples with high resolution and thus holds great potential in biomedical applications. Contrast agents play essential roles in optoacoustic imaging, and they have been widely explored and applied as probes and sensors in recent years, leading to the emergence of a variety of new contrast agents. In this review, we aim to summarize the latest advances in emerging contrast agents, especially the activatable ones which can respond to specific biological stimuli, as well as their preclinical and clinical applications. We highlight their design strategies, discuss the challenges and prospects in multispectral optoacoustic imaging, and outline the possibility of applying it in clinical translation and public health services using synthetic contrast agents.